2009
DOI: 10.1177/0269216309104074
|View full text |Cite
|
Sign up to set email alerts
|

Deciding about continuous deep sedation: physicians’ perspectives

Abstract: Although guidelines restrict the use of continuous deep sedation to patients with refractory physical symptoms and a short life-expectancy, its use is not always restricted to these conditions. A focus group study of physicians was conducted to gain more insight in the arguments for and against the use of continuous deep sedation in several clinical situations. Arguments in favour of continuous deep sedation for patients with a longer life-expectancy were that the overall clinical situation is more relevant th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
35
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 39 publications
4
35
1
1
Order By: Relevance
“…This study supported previous research that found decisions were collaborative, driven by patient's wishes, and supported by family and the multidisciplinary team. 21,22 Other studies had found that the setting, individual values, and culture could impact decisions, 23,24 but at this site, nurses perceived the culture as supportive and collaborative, and consensus was reached easily, which contradicted some previous findings. 25 …”
Section: Decisions About Intolerable Sufferingcontrasting
confidence: 62%
“…This study supported previous research that found decisions were collaborative, driven by patient's wishes, and supported by family and the multidisciplinary team. 21,22 Other studies had found that the setting, individual values, and culture could impact decisions, 23,24 but at this site, nurses perceived the culture as supportive and collaborative, and consensus was reached easily, which contradicted some previous findings. 25 …”
Section: Decisions About Intolerable Sufferingcontrasting
confidence: 62%
“…It is regarded as an indispensable treatment to alleviate intolerable refractory symptoms, but it diminishes the patient's ability to communicate in the last days of life 8 10 11. Although it is argued that continuous sedation does not shorten life when its use is restricted to the patient's last days of life,12 13 physicians sometimes indicate using it with the intention of hastening death 1416. These issues illustrate that the clinical decision-making about continuous sedation until death is very precarious, and have stimulated the development of frameworks and guidelines regarding this very delicate part of medical practice 10 1719…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, it is used frequently: comparable nationwide studies in Europe show frequencies of 2.5% to 16% of all deaths. [6][7][8] An important reason for continuous deep sedation being thought of as controversial is the possible association of this practice with the hastening of death, [9][10][11] although it is also argued that palliative sedation does not shorten life when its use is restricted to the patient's last days of life. 12,13 Guidelines for palliative sedation often advise physicians to titrate sedatives, 2,3,14 which means that the dosages of sedatives are adjusted to the level needed for proper relief of symptoms.…”
mentioning
confidence: 99%